The short-term effect of glucosamine-sulfate, nonanimal chondroitin-sulfate, and S-adenosylmethionine combination on ultrasonography findings, inflammation, pain, and functionality in patients with knee osteoarthritis: A pilot, double-blind, randomized, placebo-controlled clinical trial - Zoran Veličković,; Slavica Pavlov Dolijanović,; Nikola Stojanović,; Saša Janjić,; Ljiljana Kovačević,; Ivan Soldatović,; Goran Radunović, (Archives of Rheumatology, 2023)
Objectives: This study aimed to investigate the efficacy of glucosamine-sulfate (GS), nonanimal chondroitin-sulfate (naCS), and S-adenosylmethionine (SAMe) combination on ultrasound findings, inflammation, pain, and functionality in knee osteoarthritis. Patients and methods: In the prospective, randomized, double-blind, placebo-controlled pilot study conducted between August 2019 and November 2019, 120 participants (28 males, 92 females; mean age: 66.4±7.9 years; range, 42.4 to 74.5 years) were randomized at a 1:1:1 ratio to the placebo group, the first experimental group (a combination of GS, naCS, and SAMe was administered to the experimental groups. The first experimental group received 375 mg of GS, 300 mg of naCS, and 100 mg of SAMe, whereas the second experimental group received 750 mg of GS, 600 mg of naCS, and 200 mg of SAMe). Laboratory (erythrocyte sedimentation rate, C-reactive protein, tumor necrosis factor alpha, interleukin [IL]-1β, IL-6, IL-17), clinical (Visual Analog Scale [VAS], short form health survey [SF-36], the Western Ontario and McMaster Universities Arthritis Index [WOMAC], and the Tegner Lysholm Knee Scoring Scale [TLKS]), and musculoskeletal ultrasound (MSUS) assessments were performed at baseline and after three and six months. Results: A minor increase was observed in the second experimental group after six months using ultrasonography to evaluate articular cartilage thickness (p<0.05). The investigational product's superiority in reducing osteoarthritis ultrasonographic findings was not proven. A moderately negative association was found between cartilage thickness and VAS scores at baseline (ρ=-0.36, p<0.01), while the presence of massive osteophytes on MSUS showed a low to moderate association with all clinical outcomes. There was no difference in the delta changes between groups for the VAS, TLKS, WOMAC, and SF-36. The only serum inflammatory marker outside the reference range was IL-1β, but no significant changes were observed after six months. Conclusion: According to the results of our investigation, treatment for knee osteoarthritis should be evaluated using more objective outcomes. The most important conclusion of our study is that IP may result in a slight increase in articular cartilage thickness, which was associated with a decrease in pain intensity at baseline. Clarification of the potential influence of this combination on radiographic progression and laboratory markers of inflammation requires further exploration.